2018
DOI: 10.1039/c7dt04141a
|View full text |Cite|
|
Sign up to set email alerts
|

Nano-graphene oxide-UCNP-Ce6 covalently constructed nanocomposites for NIR-mediated bioimaging and PTT/PDT combinatorial therapy

Abstract: NIR light-induced imaging-guided cancer therapy is an encouraging route in the cancer theranostic field. Herein, we describe a novel nanoscale proposal, which is established by covalently implanting core-shell structured upconversion nanoparticles (UCNPs) with nanographene oxide (NGO) by a process utilizing polyethylene glycol (PEG), and consequently loading Chlorin e6 (Ce6) onto the surface of NGO. The acquired NGO-UCNP-Ce6 (NUC) nanocomposites can not only be employed as upconversion luminescence (UCL) imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 54 publications
1
88
0
Order By: Relevance
“…These findings promise the potential use of this system for complete tumor ablation and metastasis prevention. Several research groups have designed hybrid materials comprising photosensitizer-linked graphene/GO (GO-fullerene C60) [72], RGO-Ru-PEG [73], folic acid-GO-manganese dioxide [74], GO-enwrapped SiO 2 /TiO 2 hollow nanoparticles loaded with protoporphyrin IX [75], and NGO-UCNP-Ce6 [76] for combined PTT and PDT in a single platform. Effective delivery of photosensitizers for PDT along with enhanced fluorescence imaging was achieved by Yan et al [77].…”
Section: Graphene Substrates For Photothermal Therapy and Photodynamimentioning
confidence: 99%
See 1 more Smart Citation
“…These findings promise the potential use of this system for complete tumor ablation and metastasis prevention. Several research groups have designed hybrid materials comprising photosensitizer-linked graphene/GO (GO-fullerene C60) [72], RGO-Ru-PEG [73], folic acid-GO-manganese dioxide [74], GO-enwrapped SiO 2 /TiO 2 hollow nanoparticles loaded with protoporphyrin IX [75], and NGO-UCNP-Ce6 [76] for combined PTT and PDT in a single platform. Effective delivery of photosensitizers for PDT along with enhanced fluorescence imaging was achieved by Yan et al [77].…”
Section: Graphene Substrates For Photothermal Therapy and Photodynamimentioning
confidence: 99%
“…Molecular dynamic simulation studies showed that basic amino acid residues (arginine and lysine) and aromatic residues (tryptophan, tyrosine, and phenylalanine) play a key role in binding the protein onto the surface of graphene Porphyrin-GO -U87-MG cells Photothermal therapy; brain cancer treatment [67] Aptamer-magnetic GO Indocyanine green CCRF-CEM Photothermal, photodynamic therapy [70] GO-fullerene C60 -HeLa cells Photothermal, photodynamic therapy [72] RGO-Ru-PEG Ru(II)-polypyridyl complex A549 cells Multifunctional imaging and phototherapy [73] NGO-UCNP-Ce6 Ce6 HeLa cells; U14 tumor bearing mice Up-conversion luminescence imaging and PDT/PTT [76] Polypyrrole nitrogen-doped fewlayer graphene (PPy-NDFLG)…”
Section: Importance Of Protein Coronamentioning
confidence: 99%
“…74,80 Another drawback of conventional PDT is the short wavelength of the excitation light, which is mainly located in the ultraviolet or visible region, resulting in limited penetration depth and in easy distribution by various endogenous light chromophores, such as melanin. 87 Li et al developed Nd 3+ sensitized lanthanide nanoparticles as carriers for loading PS; this UC nanoparticle relied on the excitation light wavelength of 808 nm that bypassed the defects of traditional Yb 3+ ions sensitized UC nanoparticles and achieved effective imaging-guided PDT without impairing imaging signals. ICG, IR820 and IR780 are multifunctional PS that rely on NIR laser (808 nm) irradiation with improved penetration and efficacy of PDT.…”
Section: Recent Advance Of Nanoparticle-based Pdtmentioning
confidence: 99%
“…86 Gulzar et al designed graphene oxide as a carrier with chlorin e6 loading under 808 nm NIR laser excitation for imagingguided PDT. 87 Li et al developed Nd 3+ sensitized lanthanide nanoparticles as carriers for loading PS; this UC nanoparticle relied on the excitation light wavelength of 808 nm that bypassed the defects of traditional Yb 3+ ions sensitized UC nanoparticles and achieved effective imaging-guided PDT without impairing imaging signals. 88 The efficacy of PDT is restricted by hypoxic tumor microenvironment owing to the imbalance between the supply and consumption of oxygen in solid tumors.…”
Section: Recent Advance Of Nanoparticle-based Pdtmentioning
confidence: 99%
“…Utilizing upconversion nanocrystals is a promising method for NIR light-mediated bioimaging and photothermal and photodynamic therapy. Gulzar et al [131,174] covalently functionalized nGO with core-shell structured unconversion nanoparticles in the steps as shown in Figure 7. Oleic acid stabilized NaGdF 4 : Yb 3+ , Er 3+ was firstly synthesized followed by the formation of a NaGdF 4 : Nd 3+ , Yb 3+ shell around it.…”
Section: Nanoparticle Functionalized Graphene-based Materialsmentioning
confidence: 99%